Intervensi Penanganan Psikologis pada Pengguna NAPZA - Khasanah, Widya Nur; Anshori, Rika Oktaviani; Lestari, Prita; Aryanti, Khofifah; Maulani, Zulviana Nurahma; Farida, Reica Vina; Hasan, Laila Azmila; Sunari, Tia Bella; Hilmayasari, Rizma; Rohmawati, Rohmawati; Carolin, Wafa Nabiilah; Verdyan, Nesya Pradini; Hendrita, Noni; Sianturi, Renta (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2022)
Introduction: Drug abuse is a problem that occurs at the national, regional and global levels. Drug dependence can lead to psychological effects such as emotions, violent behavior, insecurity, depression, and so on. Psychological impacts due to drug dependence can be handled in the form of treatment, rehabilitation or other interventions. Written articles using a Literature Review approach to 11 articles on psychological treatment of drug abuse in the 2017-2021 period using the keywords